Managing Trust and Achievement Motivation to Improve Teacher Engagement in Private Vocational Schools in Bogor Regency - Yosa Taufiq Ismail; Sri Setyaningsih; Soewarto Hardhienata (International journal of technology and education research, 2025)
This study aims to examine the influence of trust management and achievement motivation on teacher engagement in private vocational schools in Bogor Regency. The method used in this study is a quantitative approach with a survey design. The research sample consisted of 215 teachers in various private vocational schools in Bogor Regency who were selected randomly. Data collection was conducted through a questionnaire measuring three main variables: trust management, achievement motivation, and teacher engagement. The results of the study indicate that good trust management has a significant positive influence on the level of teacher engagement, with an average score of 4.3 (standard deviation 0.84). Additionally, achievement motivation also significantly contributed to increased teacher engagement, with an average score of 4.3 (standard deviation 0.81). Multiple linear regression analysis revealed that trust management and achievement motivation simultaneously had a significant impact on teacher engagement (p-value < 0.01). The practical implications of this study are the need for school management to improve communication transparency, provide adequate reward programs, and offer professional development opportunities for teachers. This study provides important insights for education managers to improve the quality of learning through increased teacher engagement.